EXPERIMENTAL STRESS CONCENTRATION FACTOR IN CONCRETE-FILLED STEEL TUBULAR T-JOINTS. (November 2018) - Musa, Idris A.; Mashiri, Fidelis R.; Zhu, Xinqun; Tong, Lewei
Abstract: An experimental investigation of stress concentration factor (SCF) in Steel circular hollow section brace welded to concrete-filled circular hollow section chord (CHS-to-CFCHS) T-joints has been performed under axial tension, axial compression, in-plane bending and out-of-plane bending. The distribution of SCF around the welded brace-to-chord intersection on both the brace and chord has been investigated using three CHS-to-CFCHS T-joint specimens. The experimental SCF results have been compared with the predicted SCF in empty T-joints. The relationship between the maximum SCF in relation to parameter β, with fixed other geometrical parameters, has been investigated for the basic load conditions. The experimental maximum SCF under axial tension has been compared with the predicted maximum SCF from parametric equations for CHS-to-CFCHS T-joints previously developed by the authors. The results show that the concrete has a significant effect in reducing the SCF, mostly under axial tension and the parametric equations for predicting SCFs in empty T-joints are not suitable for CHS-to-CFCHS T-joints. The effect of parameter β on the maximum SCF in CHS-to-CFCHS T-joints is significant under axial tension and out-of-plane bending moment. Highlights: Concrete infill effectively reduces the SCF under all loading cases. Parametric equations for predicting SCFs in empty T-joints are not suitable for CFST T-joints. Trend in variation of the maximum SCF with β in CFST T-joints under axial tension is opposite to that in empty T-joints Effect of parameter β on the maximum SCF in CFST T-joints is significant under axial tension and out-of-plane bending moment. Parameter β has little effect on the SCF in both CFST and empty T-joints under in-plane bending.